Digital transformation and economic growth (on the example of the Belarusian economy) - Goloventchik, Галина G.; Kovalev, Mikhail M. (Journal of the Belarusian State University. Economics, 2018)
The aim of the article is to forecast the potential economic growth of Belarus and the impact of the digital economy on this potential, considering the global trends forming the new digital economy of the XXI century. The article suggests a methodology of measuring the index of readiness for the digital economy. On the basis of this methodology a model is built of calculating the modernization rate, which is necessary for evaluation of the total factor productivity which determines the economic growth rate.
Keywords: economic growth; new economy; digital economy